The Impact Of Key Service Quality Factors On Customer Loyalty: A Study On Tokopedia - Siahaya, Janice Carysa (Dinasti Publisher, 2025)
E-commerce transactions in Indonesia continued to increase starting in 2017 according to Bank Indonesia records. Moreover, during the Covid-19 pandemic, the use of digital media is increasingly widespread among the Indonesian community, as consumption on online marketplace platforms is increasing, one of which is a marketplace made by the nation's children, Tokopedia. This study was conducted to determine the effect on Customer Loyalty of Tokopedia users in Kediri with the aim to use the seven variables in identifying Customer Loyalty in Tokopedia. This study used SPSS 22.0 software. The sample used in this study is Tokopedia users aged 18-60 years, domiciled in Kediri, male or female, have installed applications in the last 6 months, have made purchases 2 times in the last 6 months, and have contacted Tokopedia customer service in the last 6 months. The number of respondents used as a sample of research is 130 by using the sampling method used is non-probality sampling.